Relationship between Signal Intensity Change of the Spinal Cord on MRI and Motor Myelopathic Severity in Patients with Cervical Spondylotic Myelopathy (Journal of National Institute of Neurosciences Bangladesh, 2017)
Background: Diagnosis of cervical spondylotic myelopathy (CSM) can be challenging due to subtle symptoms and insidious onset; however, there is a relationship between signal intensity change of the spinal cord on MRI and cervical spondylotic myelopathy. Objective: The purpose of this present study was to find out the relationship between signal intensity change of the spinal cord on MRI and motor myelopathic severity in patients with CSM.Methodology: This cross-sectional study was carried out in the Department of Neurosurgery at Banghabandhu Sheikh Mujib Medical University (BSMMU), Dhaka from October, 2011 to March, 2013 for a period of one and half year. All patients presented with cervical spondylotic myelopathy were included in this study. MRI of cervical spine was performed to all patients.Results: A total number of 36 patients with cervical spondylotic myelopathy were included in this study. Among the 36 study patients, all had normal intensity in the spinal cord on sagittal T1WI of MRI; however, there was variable intensity on sagittal T2WI of MRI. Low Nurick score was found in 24(66.6%) patients who had type 0 signal intensity on (T2WI) MRI. High Nurick score was found in 3(8.3%) patients who had type 0 signal intensity on (T2WI) MRI. Low Nurick score was found in 2(5.5%) patients who had type 1 signal intensity on (T2WI) MRI. High Nurick score was found in 6(16.6%) patients who had type 1 signal intensity on (T2WI) MRI. Only 1 patient (2.7%) having high Nurick score (3-5) had type-2 signal intensity on (T2WI) MRI (p